Mathematics teachers’ professional influence within teacher communities: the role of work experience and pedagogical content knowledge - Grigaliūnienė, Monika; Lehtinen, Erno; Gruber, Hans; Palonen, Tuire (Informa UK Limited, 2026)
This study investigated if mathematics teachers' professional experience or pedagogical content knowledge (PCK) could predict how often colleagues seek their colleagues for advice. Ninety-three Lithuanian secondary school mathematics teachers participated. The analysis found that only professional experience, not PCK, predicted how often a teacher was consulted. Seniority primarily influenced whether teachers were sought out for advice on pedagogical matters. Interestingly, there was a significant negative correlation between professional experience and PCK. Cluster analysis identified four groups; teachers with less experience had the highest PCK but were rarely consulted. Meanwhile, more experienced teachers, regardless of whether they had high or low PCK, were frequently asked for advice. Both experienced groups were equally recognised as valuable sources of advice by their peers. The study suggests further research is needed to understand how PCK evolves over a teacher's professional development and how its relevance may change over time.